The temporal effects of relative and firm-level absorptive capacity on interorganizational learning - Schildt, Henri; Keil, Thomas; Maula, Markku (Strategic management journal, 2012)
We examine how determinants of absorptive capacity influence learning in alliances over time. Using longitudinal patent cross-citation data, we find an inverted U-shaped pattern over time that is influenced by firm-level and relational factors. Technological similarity only modestly increases learning in the initial stages of a relationship, but moderate levels substantially increase knowledge flows later in the alliance. High technological diversity is related to higher initial learning rates, but the effects diminish over time. Somewhat surprisingly, research and development intensity is negatively related to initial learning rates but has a considerable positive effect later in the relationship. We suggest that initial learning rates in alliances may be constrained by the capacity to absorb knowledge, while later-stage outcomes are constrained by exploitation capacity.